Beyond Competition: Musabaqah Tilawatil Qur'an Training and Young Participants' Interest in and Love for the Qur'an at Sanggar Al-Fatih - Johan Daniransyah; Idris Siregar (Journal of Indonesian Islamic Studies, 2026)
Musabaqah Tilawatil Qur'an (MTQ) is commonly understood as a Qur'anic recitation competition, yet its educational contribution to participants' sustained interest and affective attachment to the Qur'an remains insufficiently examined. This study analyzes the implementation of MTQ training and its role in fostering participants' interest in and love for the Qur'an at Sanggar Al-Fatih, Tebing Tinggi. A qualitative case-study design was employed. Data were obtained through direct observation, in-depth interviews with administrators, trainers, and participants, and analysis of program documentation. The data were condensed, organized thematically, and interpreted through iterative conclusion drawing, while source and method triangulation were used to strengthen credibility. The findings show that training was conducted progressively through instruction in makharij al-huruf, tajwid, nagham, breathing and voice control, interpretive recitation, and performance readiness. Regular practice increased participants' enthusiasm, discipline, confidence, and willingness to study the Qur'an beyond competition preparation. Intensive interaction with Qur'anic verses also encouraged habitual recitation, participation in religious activities, moral self-regulation, and a stronger sense of closeness to the Qur'an. These outcomes were supported by competent trainers, parental encouragement, senior role models, and a conducive religious environment, but constrained by differences in initial ability, limited practice time, and funding. The study concludes that MTQ training can function as sustained non-formal Qur'anic education when technical coaching is integrated with motivation, habituation, and character formation.